Brief Report: Estimating Disease Activity Using Multi‐Biomarker Disease Activity Scores in Rheumatoid Arthritis Patients Treated With Abatacept or Adalimumab. Issue 9 (25th August 2016) - Fleischmann, Roy; Connolly, Sean E.; Maldonado, Michael A.; Schiff, Michael
Abstract : Objective: To assess the ability of a multi‐biomarker disease activity (MBDA) test (Vectra DA) to reflect clinical measures of disease activity in patients enrolled in the AMPLE (Abatacept Versus Adalimumab Comparison in Biologic‐Naive RA Subjects with Background Methotrexate) trial. Methods: In the AMPLE trial, patients with active rheumatoid arthritis (RA) who were naive to biologic agents and had an inadequate response to methotrexate were randomized (1:1) to receive subcutaneous abatacept (125 mg every week) or subcutaneous adalimumab (40 mg every 2 weeks), with background methotrexate, for 2 years. The MBDA score was determined using serum samples collected at baseline, month 3, and years 1 and 2. The adjusted mean change from baseline in the MBDA score was compared between the abatacept and adalimumab treatment groups. Cross‐tabulation was used to compare the MBDA score with the following clinical measures of disease activity: Clinical Disease Activity Index (CDAI), Simplified Disease Activity Index (SDAI), Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP), and Routine Assessment of Patient Index Data 3 (RAPID‐3). Results: In total, 318 patients were randomized to receive abatacept, and 328 were randomized to receive adalimumab; MBDA data were available for 259 and 265 patients, respectively. No association between the MBDA score and disease activity defined by the CDAI, SDAI, DAS28‐CRP, or RAPID‐3 in the abatacept and adalimumab treatment groups was observed. Conclusion: The MBDA score did not reflect clinical disease activity in patients enrolled in AMPLE and should not be used to guide decision‐making in the management of RA, particularly for patients who receive abatacept or adalimumab as the first biologic agent.